2014
DOI: 10.1177/0887403414521462
|View full text |Cite
|
Sign up to set email alerts
|

Examining Public Preferences for the Allocation of Resources to Rehabilitative Versus Punitive Crime Policies

Abstract: Fear of crime has been recognized as one of the driving forces underlying the punitive turn in the criminal justice system. Despite this, evidence suggests that rehabilitative efforts are still supported by the general public. The current study uses a national random sample to examine the impact of fear on public preference for allocating resources to rehabilitative versus punitive criminal justice system policies. Contrary to prior studies, respondents are forced to make a choice between punitive and rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 50 publications
5
54
0
1
Order By: Relevance
“…More recently, scholars have used methods that probe support for rehabilitation by using forced‐choice questions that pit treatment/prevention versus punishment/imprisonment and by assessing the public's willingness to pay for competing policy alternatives. Support for rehabilitation has consistently been found in these studies (e.g., Baker, Cleary, Pickett, and Gertz, ; Baker, Metcalfe, Berenblum, Aviv, and Gertz, ; Cohen, Rust, and Steen, ; Nagin et al., ; Piquero and Steinberg, ).…”
Section: Public Opinion and Public Policymentioning
confidence: 73%
“…More recently, scholars have used methods that probe support for rehabilitation by using forced‐choice questions that pit treatment/prevention versus punishment/imprisonment and by assessing the public's willingness to pay for competing policy alternatives. Support for rehabilitation has consistently been found in these studies (e.g., Baker, Cleary, Pickett, and Gertz, ; Baker, Metcalfe, Berenblum, Aviv, and Gertz, ; Cohen, Rust, and Steen, ; Nagin et al., ; Piquero and Steinberg, ).…”
Section: Public Opinion and Public Policymentioning
confidence: 73%
“…That is, in an era that some consider "post-racial," it is clear that social science can better illuminate how situational and contextual factors, in addition to race, enhance the perceived association between African-Americans and crime. Extensive sociological research has already explored how a general fear of crime often explains support for policies that disproportionately impact Black communities (e.g., Baker, Metcalfe, Berenblum, Aviv, & Gertz, 2015;Unnever & Cullen, 2010;Unnever, Cullen, & Jones, 2008), suggesting that racial disparities in criminal justice outcomes are allowed to occur because race is no longer perceived to be the explicit and direct cause of punishment (e.g., Alexander, 2010;Lopez, 2014). Others have similarly suggested that attitudes about poverty are being used to justify racially discriminatory policies (e.g., Costelloe, Chiricos, & Gertz, 2009;Hogan, Chiricos, & Gertz, 2005).…”
Section: Reconceptualizing Anti-black Attitudesmentioning
confidence: 99%
“…While we have seen an increase in research on public attitudes towards criminal justice practice in the past two decades (e.g. Baker, Metcalfe, Berenblum, Aviv, & Gertz, 2015, Enns, 2014Hough and Roberts, 1998;Darley, Carlsmith and Robinson, 2000;Roberts, Stalans, Indermaur, & Hough, 2003), there is little empirical research on this topic within a Scandinavian context.…”
Section: Introductionmentioning
confidence: 99%